Cooperation between academic workers: deontological considerations in the aspect of Poland = Kwestia współpracy między pracownikami akademickimi: rozważania deontologiczne w aspekcie polskim - Nowakowski, Piotr T. (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author focused on deontological considerations regarding the cooperation between academic workers in the reality of Polish universities. In view of the possible irregularities that threaten this cooperation, it was investigated what solutions to this issue are offered by the ethical codes of universities, but also how this problem is perceived by students, who tend to be critical and keen observers.
Keywords: academic worker; academic community; intra-academic collaboration; academic ethical code; academic deontology; pracownik akademicki; środowisko akademickie; współpraca wewnątrzakademicka; akademicki kodeks etyczny; deontologia akademicka